2009
DOI: 10.2337/dc09-0900
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Diabetes Screening

Abstract: OBJECTIVETo determine the rate of adherence to postpartum glycemic testing in women with gestational diabetes mellitus (GDM) and the performance of fasting plasma glucose (FPG) versus the 75-g oral glucose tolerance test (OGTT) in detecting postpartum glucose intolerance.RESEARCH DESIGN AND METHODSThe study was a retrospective cohort of 1,006 women with GDM attending a pregnancy diabetes clinic.RESULTSPostpartum screening was completed in 438 (48%) women. Women nonadherent to testing had higher parity (1.10 vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
64
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 14 publications
12
64
1
Order By: Relevance
“…The short-term follow-up rate found in this study (18.5% at 6 months) is comparable with those reported in Canada: 14.3-48%; 24,42 somewhat worse than the US: 38-54%; 22,25,26 and considerably worse than Australia: 70-73%. 29,43 The GDM Recall Register in Australia may explain this large discrepancy.…”
Section: Comparison With Existing Literaturesupporting
confidence: 78%
See 2 more Smart Citations
“…The short-term follow-up rate found in this study (18.5% at 6 months) is comparable with those reported in Canada: 14.3-48%; 24,42 somewhat worse than the US: 38-54%; 22,25,26 and considerably worse than Australia: 70-73%. 29,43 The GDM Recall Register in Australia may explain this large discrepancy.…”
Section: Comparison With Existing Literaturesupporting
confidence: 78%
“…26 There are limited published data on the long-term follow-up of females who have had GDM. Rates of up to 35% have been reported in the US 24 and 39% in the UK, 33 but again only through self-reported survey responses. This is somewhat better than the annual long-term screening rates found here from patient records: around 20%.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The use of medication, either insulin (8)(9)(10)(11) or oral agents (8) for glycemic control during pregnancy, is associated with persistent hyperglycemia, whereas body mass index (BMI) (10), race (9,11) and other risk factors (1-h blood glucose in diagnostic OGTT (11), previous GDM (9), parity rates (10)) are described in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the OGTT, single glucose and haemoglobin A1c levels have consistently been shown to be insensitive screening tests for type 2 diabetes in the postpartum period. [25][26][27][28][29][30][31][32][33] Recently, Capula et al found that 32.3% of women with previous GDM completed an OGTT within 6 and 12 weeks postpartum. Prepartum counselling and a diagnosis of polycystic ovarian syndrome were the strongest predictors of adherence to completing a postpartum OGTT.…”
Section: Discussionmentioning
confidence: 99%